2009
DOI: 10.1007/s10995-009-0486-x
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Katrina-Related Maternal Stress, Maternal Mental Health, and Early Infant Temperament

Abstract: To investigate temperament in infants whose mothers were exposed to Hurricane Katrina and its aftermath, and to determine if high hurricane exposure is associated with difficult infant temperament. A prospective cohort study of women giving birth in New Orleans and Baton Rouge, LA (n=288) in 2006–2007 was conducted. Questionnaires and interviews assessed the mother’s experiences during the hurricane, living conditions, and psychological symptoms, two months and 12 months postpartum. Infant temperament characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 38 publications
3
65
6
1
Order By: Relevance
“…Interestingly, the present results are in line with those obtained for women who became pregnant post-Hurricane Katrina by Tees et al (9): in both studies, objectively defined disaster-related experiences had no direct effects on temperament status. However, in the present study, objective hardship combined with maternal illness/infection to explain a portion of the infants' fussy/difficult ratings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the present results are in line with those obtained for women who became pregnant post-Hurricane Katrina by Tees et al (9): in both studies, objectively defined disaster-related experiences had no direct effects on temperament status. However, in the present study, objective hardship combined with maternal illness/infection to explain a portion of the infants' fussy/difficult ratings.…”
Section: Discussionsupporting
confidence: 93%
“…One study that assessed the effect of maternal exposure to a natural disaster found that while hurricanerelated experiences (i.e., damage to home, life in danger, walking through floodwaters) were unrelated to temperament status, increased number of hurricane-related post-traumatic stress disorder symptoms were related to more difficult infant temperaments (9). Furthermore, high levels of maternal cortisol during pregnancy have also been shown to be associated with poorer infant temperaments either directly (10) or by its effect on birth weight (11).…”
mentioning
confidence: 99%
“…Furthermore, PMNS has been largely addressed as normative stress in everyday life (Rubonis and Bickman, 1991) that can be increased by other factors such as maternal psychopathology and socioeconomic status. Fewer prospective human studies have examined the effects of large-scale disastrous events (e.g., Quebec Ice Storm, Hurricane Katrina, and World Trade Center terrorism) on developmental programming (Brand et al, 2006; Huizink et al, 2007; King and Laplante, 2005; Kuvacic et al, 1996; Laplante et al, 2016, 2008; Meijer, 1985; Tees et al, 2010; Yehuda et al, 2005), and the findings are inconsistent regarding the impact of maternal stress during pregnancy and temperament. When Laplante et al (2016) studied the impact of the Quebec Ice Storm, they found that elevated levels of mother’s subjective stress reaction to the ice storm during pregnancy were associated with difficult temperament characteristics (i.e., fussiness, dullness, and attention seeking) among 6-month old offspring.…”
Section: Introductionmentioning
confidence: 99%
“…322, 333). Most current studies focus on mothers who suffered stressful events in childhood, who are found to be less sensitive, less available, less involved, and more hostile and intrusive (Davies, Slade, Wright, & Stewart, 2008;Kaitz, Levy, Ebstein, Faraone, & Mankuta, 2009;Lyons-Ruth & Block, 1996;Tees et al, 2010;Van et al, 2012). Little is known about fathers' experiences of early life stressors and how they relate to their involvement with their own children in later adulthood.…”
Section: Gaps In Past Researchmentioning
confidence: 99%